Penyebaran Link Phising Kuota Kemendikbud Terhadap Kesadaran Informasi Pribadi Di Kalangan Mahasiswa UNINUS - Akmal Ramadhan; Muhammad Alwi Alhafidh; Muhamad Diki Firmansyah (IHSA Institute, 2022)
Hoaxes are becoming one of the things that are increasingly found in todays digital era. The types of hoaxes circulating in the community are also very diverse, one of which is the Ministry of Education and Culture quota phishing link hoax. This hoax is targeting the personal data of students and people who need internet quota during this pandemic. For this reason, we want to find out how aware Uninus students are about the importance of personal data security. This study uses descriptive approach, and data collection technique is through interviews and questionnaires. This type of research data is primary data, and the research subjects are Uninus students. The object of this research is the awareness of Uninus students towards personal information, the informants are class A students of the Communication Studies study program. As a result, the informants admitted that they had received phishing links from the Ministry of Education and Culture quota and knew that phishing links could threaten personal data and could also cause material and non-material losses. They also know the steps to avoid becoming a victim of phishing links and the informants admitted that they are very aware of the importance of personal information security.